P23 500 consecutive referrals to a DGH sleep service: how useful is the Epworth?. (2nd December 2011) - White, L H; Backway, S; Kerry, A; Stanton, A; Juniper, M
Abstract : Introduction and Objectives: Our sleep service offers assessment and treatment of sleep-disordered breathing (SDB). Our commissioners suggested that patients with an Epworth Sleepiness Score (ESS) = 9 did not require assessment. We assessed the characteristics of patients referred and usefulness of baseline ESS. All patients referred for assessment of SDB were entered onto a database prospectively from October 2009 to June 2011. Baseline data recorded was: referral source, demographics, ESS, sleep study type, oxygen desaturation index >4% (ODI), study interpretation, treatment decision. Results: 500 patients were referred, most commonly by GP (n=349), endocrinology (n=50), respiratory (n=34) and ENT (n=29). 365 patients were male, mean age (±SD) 51.3±13.5 years. 476 patients (95.2%) underwent respiratory polygraphy (377 inpatient, 99 at home) and 24 (4.8%) overnight oximetry. Initial mean ESS (±SD) was 13.3±6.0 and was positive (=10) in 354 patients (70.8%). SDB was demonstrated in 309 patients (61.8%) and periodic limb movements in 8. Positivity rates varied with referral source (GP–64.8%, diabetes–55.2%, respiratory–67.6%, ENT – 55.2%) and sleep study type (inpatient polygraphy-60.2%, home polygraphy-76.8%, oximetry-58.3%). Diagnosis was obstructive sleep apnoea (OSA) (n=246, 15 with coexistent hypoventilation), upper airways resistance (n=56), obesity hypoventilation (n=4), central sleep apnoea (n=2) and COPD-related nocturnal hypoxia (n=1). Median ODI for all studies was 9 (range 0–150). OSA was mild in 72 patients (29.3%), moderate in 65 (26.4%) and severe in 106 (43.1%). ODI was <5 in 3 patients (1.2%) but the study deemed positive. Following clinical assessment, 269 patients (53.8%) commenced CPAP, of whom 36 (13.4%) had an initial ESS=9. In these patients, severity of SDB did not relate to baseline ESS (mean ODI 32.0 (ESS=9) vs 30.5 ESS=10)). Of the 106/500 patients with ESS=9, 54.3% had a positive study and 33.3% were commenced on CPAP, as compared to 65.5% and 58.8% respectively of patients with ESS=10. Conclusion: We identified a reasonable percentage of patients referred with suspected SDB. A significant number of such patients had a normal ESS, which may underestimate symptoms warranting CPAP. A negative ESS should not preclude sleep referral and should be used with caution when designing referral criteria.